Effect of bonding protocol on shear bond strength of orthodontic brackets: An in vitro study - Munhoz,Tais (2014)
The aim of this study was to evaluate the shear bond strength of bracket composites as a function of the application of flow adhesive prior to the composite and light curing time.Material and methods:Freshly extracted bovine permanent central incisors (50) were acid etched and divided into four groups varying the attachment protocol: (1) no adhesive, composite light-cured for 20s; (2) no adhesive, composite light-cured for 40s; (3) application of adhesive, composite light-cured for 20s; and (4) application of adhesive, composite light-cured for 40s. For comparison, a chemically cured system was used accordingly to the manufacturer instructions. The samples were stored in distilled water (37ºC) for 24 hours prior to the shear test (0,75mm/min) and the adhesive remnant index (ARI) was registered for each tooth.Results:The present in vitro findings showed that both variables, application of adhesive and light curing time, influenced the bond strength of orthodontic brackets. Brackets bonded without adhesive present lower resistance to shear forces (p=0.05) than the samples bonded with adhesive. Higher bond strength values were found for longer light curing times, though statistical difference (p=0.05) was only observed between groups (3) and (4). ARI results show lower scores for extended light curing times. Although the variables in this study significantly affect the shear bond strength of orthodontic brackets, all the experimental groups show bond strength values greater than the normally accepted in the current literature.